Assessing Tensile and Shear Properties of Recycled Sustainable Asphalt Pavement (Journal of Engineering, 2015)
Hot mix recycling of asphalt pavements is increasingly being used as one of the major rehabilitation methods by various highway agencies. Besides general savings in costs and energy expended, it also saves our natural resources and environment.  Recycling process presents a sustainable pavement by using the old materials that could be reclaimed from the pavement; these materials could be mixed with recycling agents to produce recycled mixtures. The important expected benefits of recycling process are the conservation of natural resources and reduction of environmental impact. The primary objectives of this work are evaluating the Tensile and Shear Properties of recycled asphalt concrete mixtures, In addition to the resistance to moisture damage. The impact of implementing three types of recycling agents on asphalt concrete properties was also investigated. For this purpose, old materials reclaimed from field, (100% RAP), virgin filler at 3 percent content by weight of mixture and three types of recycling agents ( soft asphalt cement of penetration grade 200-300, soft asphalt cement of penetration grade 200-300 blended with 4% silica fumes and soft asphalt cement of penetration grade 200-300 blended with 6% fly ash ) at 1.5% content by weight of mixture have been implemented and used to prepare recycled mixtures. Mixtures were subjected to the following tests: Marshall Test (12 specimens), indirect tensile strength test at 20ºC, 25ºC, 40ºC, and 60ºC (48 specimens), indirect tensile ratio ( 12  specimens), double punch shear test (12 specimens).It was found that using (soft asphalt cement blended with silica fumes) as a recycling agent revealed better performance results than the other type of recycling agent. The percentages of variation for recycled mixtures with recycling agent of (soft asphalt cement blended with silica fume) when compared to aged mixture were ( -13.8%, -25.05%, 229.5%, -47.67%, ) for properties of ( Marshall stability, indirect tensile strength at 60ºC, tensile strength ratio, double punch test,), respectively.